2009
DOI: 10.2337/db08-1651
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Decline in β-Cell Proliferation Restricts the Capacity of β-Cell Regeneration in Mice

Abstract: OBJECTIVE The aim of this study was to elucidate whether age plays a role in the expansion or regeneration of β-cell mass. RESEARCH DESIGN AND METHODS We analyzed the capacity of β-cell expansion in 1.5- and 8-month-old mice in response to a high-fat diet, after short-term treatment with the glucagon-like peptide 1 (GLP-1) analog exendin-4, or after streptozotocin (STZ) administration. RESULTS Young mice responded to high-fat diet by increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
308
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(328 citation statements)
references
References 42 publications
18
308
0
2
Order By: Relevance
“…1 Similarly, aging can induce a distinct gene expression program in mouse islets, leading to a decrease in the expression of a small number of genes, including Isl-1. [2][3][4][5] Taken together, these findings suggest that a decrease in Isl-1 expression might contribute to the pathophysiology of the disease and an increase in Isl-1 expression might be beneficial for a β-cell to maintain its full functionality.…”
Section: Introductionmentioning
confidence: 84%
“…1 Similarly, aging can induce a distinct gene expression program in mouse islets, leading to a decrease in the expression of a small number of genes, including Isl-1. [2][3][4][5] Taken together, these findings suggest that a decrease in Isl-1 expression might contribute to the pathophysiology of the disease and an increase in Isl-1 expression might be beneficial for a β-cell to maintain its full functionality.…”
Section: Introductionmentioning
confidence: 84%
“…These antiapoptotic effects involve the phosphoinositide 3-kinase [PI3K]/Akt, extracellular signal-regulated kinase1/2 (ERK1/2) and cAMP/PKA pathways [109]. Although ageing is characterised by a low level of beta cell proliferation, mice treated with exendin-4 at different ages show low glucose levels, suggesting a potential beneficial effect in ageing [110].…”
Section: Contributors To Maintenance Of Islet Cell Mass In Adult Rodentsmentioning
confidence: 99%
“…In addition, the dramatic age-dependent decline of pancreatic beta cell replication in response to diverse insults (high-fat diet, streptozotocin administration or short-term treatment with the GLP-1 analogue exendin-4) has been correlated by Tschen et al [110] with an increase in Bmi1 levels, a polycomb group protein that regulates the Ink4a locus and modulates the ability of the beta cell mass to expand. Interestingly, a systemic factor has been considered responsible for increasing the proliferation rate of old pancreatic beta cells when parabiosed to young mice [147].…”
Section: Old Agementioning
confidence: 99%
“…It has been reported that BCM is increased by 20 to 50% in obese adult humans without diabetes (8,11), to a smaller degree than in rodents, which usually show a two-to threefold increase (4,5), consistent with lower b-cell turnover in adult humans. Recently, we have also reported that in the Japanese population, no significant increase in BCM was observed in obese adults without diabetes (12).…”
mentioning
confidence: 94%
“…In rodents, b-cells have been shown to be able to adaptively increase in response to an increased insulin demand such as obesity or pregnancy (3)(4)(5). However, b-cell proliferation in humans has been reported to rapidly decrease within 5 years after birth, and only minimal b-cell proliferation is observed in adults (6)(7)(8).…”
mentioning
confidence: 99%